Internalisasi Furudul Ainiyah dalam Meningkatkan Kemampuan Membaca Al-Quran Santri Madrasah Diniyah Raudlatul Muta’allimin di Kraksaan Probolinggo - Ainul Yakin (GUYUB: Journal of Community Engagement, 2024)
This community service program aims to determine the internalization method of Furudlul Ainiyah (FA), the impact, supporting and inhibiting factors of FA internalization in Madrasah Diniyah Raudlatul Muta'allimin students. This program used an educational and participatory approach to achieve Al-Quran learning targets. This program results showed that: 1). FA internalization was focused on learning the Al-Quran using the method of listening, reading, introducing makharijul letters and writing hijaiyah letters using the Iqra' ang Tartila textbook. 2). The impact of FA internalization could introduce students to hijaiyah letters, makharijul letters and how to read the Al-Quran more effectively. The santri were not only able to read, but also memorize and write. 3). Supporting factors for FA internalization were qualified companions, limited classes and the enthusiasm of students. Meanwhile, the obstacles were inadequate learning facilities, lack of discipline of mentors and students in learning.